Penerapan Model Pembelajaran Kooperatif Tipe TGT (Teams Games Tournament) Berbantuan Media Monopoli - Mala Aftiani; Novianti Mandasari; Elya Rosalina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completeness of social studies learning outcomes after applying the Cooperative Learning Model Type TGT (Teams Games Tournament) Assisted by Media Monopoly in Class IV Social Studies Learning at SDN 3 Lubuklinggau City. The research method uses quasi-experiments. Data collection techniques using tests in the form of essay questions. The data obtained were analyzed using the t-test. Based on the results of research and discussion obtained an average value of 78.83 with learning completeness (94.87%). The results of the t-test analysis obtained tcount = 10.65 > ttable = 1.69 which shows that the hypothesis Hₒ is rejected and Hₐ is accepted. So it can be concluded that the learning outcomes of class IV students at SD Negeri 3 Lubuklinggau for the 2022/2023 school year after applying the cooperative learning model of the TGT (Teams Games Tournament) type assisted by monopoly media are in the significant complete category. Keywords: Teams Games Tournament, Media Monopoly, Social Studies Learning Outcomes.